ORIGINAL DHI METHOD FOR ASSESSING EPIDEMIC HAZARDS IN TRANSPORTATION SERVICES - Rafał BURDZIK (Scientific Journal of Silesian University of Technology. Series Transport)
In the situation of the global SARS-COV-2 coronavirus pandemic, epidemic threats are dominant and ubiquitous. The article attempted to estimate the hazards of virus transmission in various transport services. In the author's opinion, numerous and very serious problems in the transport sector and transport services are in this case the result of a lack of a methodical approach to the problem of epidemic threats, including infection in a global epidemic. The paper presents a proposal for an original DHI method for assessing epidemic hazards in transportation services, taking into account various hazards and routes of virus transmission (droplet and contact) based on dedicated scales of hazard evaluation and multi-criteria assessment. This methodology is named Deep Hazard Identification (DHI). The primary stage of the methodology is the identification and estimation of transmission mechanisms of pathogen that can occur in transport services. For this purpose 15 criteria and weighting factors were defined and used for a multi-criteria epidemic hazards assessment. It enables the determination of the matrix of hazard assessment separately for the passenger transport and freight transport groups, which allows for the comparison of the DHI hazard factor between different transport services.